The cytolytic activity of natural killer cells is not involved in the restriction of Mycobacterium avium growth - Florido, M (2003)
Severe combined immunodeficiency (SCID) mice were used to analyze the role of NK cells in resistance to Mycobacterium avium. The neutralization of IFN-gamma in these animals led to an exacerbation of the infection associated with a reduction in macrophage activation, suggesting a role for NK cells in innate immunity to mycobacteria. In contrast, administration of anti-asialo-GM(1) polyclonal serum or mAb specific for Thy1.2 did not affect mycobacterial growth or macrophage activation despite causing the almost complete abrogation of the natural cytolysis of a tumor cell target. Treatment with anti-asialo-GM(1)-specific serum depleted only two-thirds of the Thy1.2(+) spleen cells, and anti-Thy1.2 treatment allowed for the persistence of a small number of cells still exhibiting an NK cell marker recognized by mAb DX5 and able to express IFN-gamma as analyzed by flow cytometry. In vivo treatment of B6.SCID mice with anti-NK1.1 mAb again failed to affect resistance to infection and allowed for the persistence of 2-8% of IFN-gamma-producing cells, many of them still expressing the DX5 marker. In vitro depletion studies showed that removal of IFN-gamma-expressing cells required the combined action of anti-Thy1.2, anti-Ly49C and DX5 antibodies in the presence of complement. Our data show that resistance to M. avium mediated by NK cells is independent of their cytolytic activity, and that there is a marked phenotypic and functional heterogeneity of the NK cell lineage in vivo during infection.